Tax Competition, Excludable Public Goods and User Charges - Bernd Huber; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper provides an economic explanation for the increasing reliance of the state on revenue from user charges on excludable public goods. We develop a model with many identical countries. The government of each country levies a capital tax on the domestic production sector and supplies an excludable public good to heterogeneous households. Under immobile capital, the price on the public good is zero. Under mobile capital, in contrast, the countries engage in tax competition and each country chooses a strictly positive price on the public good. With quasi-linear preferences, the reliance on user charges is shown to increase as tax competition becomes more intensive.
Keywords: 330; excludable public goods; tax competition